The Structural Funds and the Cohesion Fund as an external sources of funding local government units - Gęsina, Milena (Management and Administration Journal, 2024)
Possession of financial resources is a key condition for the proper functioning of the local government and has a significant impact on the development. With the increasing number of tasks that local authorities must carry out, growing demand for cash. Necessary in the local government unit is to have income of their own, which are supported by external sources.